2008
DOI: 10.1038/ijo.2008.222
|View full text |Cite
|
Sign up to set email alerts
|

Visceral fat amount is associated with carotid atherosclerosis even in type 2 diabetic men with a normal waist circumference

Abstract: Objective: Our objective was to investigate whether determination of the quantity of visceral fat has an additional benefit in assessing atherosclerotic burden in men with type 2 diabetes compared with the traditional measurement of waist circumference (WC) alone. Methods: This was an observational study performed in 368 men with type 2 diabetes, consecutively enrolled in Diabetes Clinics. Common carotid artery far-wall intima-media thickness (IMT), WC and visceral fat thickness (VFT), as measured by ultrasono… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
33
1
2

Year Published

2009
2009
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(39 citation statements)
references
References 22 publications
3
33
1
2
Order By: Relevance
“…First, there is a lack of definite cutoff value for carotid atherosclerosis in PD patients. We defined carotid atherosclerosis as increased cIMT and presence of plaque to reflect focal features of carotid arteries in accordance with other studies including the general population [20,23], patients with coronary artery disease [21], non-dialysis-dependent CKD [22], HD [18], as well as PD [16,19]. Furthermore, different cutoff value (cIMT > 0.7 mm) [24] and continuous variables were also tested.…”
Section: Discussionmentioning
confidence: 99%
“…First, there is a lack of definite cutoff value for carotid atherosclerosis in PD patients. We defined carotid atherosclerosis as increased cIMT and presence of plaque to reflect focal features of carotid arteries in accordance with other studies including the general population [20,23], patients with coronary artery disease [21], non-dialysis-dependent CKD [22], HD [18], as well as PD [16,19]. Furthermore, different cutoff value (cIMT > 0.7 mm) [24] and continuous variables were also tested.…”
Section: Discussionmentioning
confidence: 99%
“…13 Another study reported the identification of a metabolically benign type of obesity, in which the subjects are generally obese, but have a relatively lower deposition of fat in the ectopic sites. 14 Thus, what seems to be more important is not how fat is accumulated, but where the body fat is located.…”
Section: Discussionmentioning
confidence: 99%
“…Average IMT was the mean of computer-based points in the region, and maximum IMT was the IMT at a maximum point of the region. 17 Plaque was defined according to the Mannheim consensus, 18 in which a plaque was diagnosed when the vessel wall thickness was >1.5 mm or when the vessel wall appeared to be at least 0.5 mm or 50% thicker than the surrounding wall.…”
Section: Cardiac Mrimentioning
confidence: 99%